Telepsychology: A Primer for Counseling Psychologists ψ - Cooper, Stewart E.; Campbell, Linda F.; Smucker Barnwell, Sara (The Counseling psychologist, 2019)
Telepsychology is having a profound influence on professional practice. Currently, however, many psychologists lack the requisite knowledge and skill to provide ethical and competent telepractice services. Moreover, the field has lagged in developing the educational and supervised experiences required to achieve competency. Yet, there is great opportunity as well. The purpose of this article is to identify the natural integration of the pillars of counseling psychology with the major domains of telepractice and to link telepractice to the values and mission of counseling psychologists. We present aspects of telepsychology including ethical and legal factors, asynchronous and synchronous practice, and group-focused practice along with technologies and the rules that govern them. We also describe interjurisdictional practice, and introduce a proposed curriculum based upon the benchmark competencies for infusion of telepsychology into training across the professional lifespan.